A method for finest ward selection for healthcare-facilities - Yasaman, Parsia; Shahryar, Sorooshian; Mohammad, Panjehpour (Romanian Society For Quality Assurance, 2020)
Today's business leaders are increasingly forced to make quick and precise decisions. Making decisions is at the core of management. To make the correct and rational decisions, a manager has to gather as much information as possible to be able to choose from various options and their imaginable consequences. In the vital organizations such as, healthcare facility (HF) in every country, make a good and precise decision is so crucial. When the manager decides to collect/select wards for his/her HF, it is an important decision to select the finest wards. This decision needs a list of comprehensive and accurate managerial criteria. The processes which presented in this study can solve this issue. To show this, in a case study, it started with gathering criteria and the name of potential wards by modified nominal group technique through interview sessions with experts. Then, weighting the potential wards based on criteria by the viewpoints of experts through the Weighted Sum Method. Finally, the wards will be priorities based on which one has the best for the HF.